Increasing the Efficiency of Students' Independent Work through Distance Learning - Hayitova Iroda Ilhomovna (International Journal of Modern Agriculture, 2021)
The article discusses the issue of increasing the effectiveness of independent work of students in distance learning.And the results of a survey of students about distance and independent learning were summarized.